Barnacle Goose Branta leucopsis abundance on Kolguev Island – current status and history of population growth - Kondratyev, Alexander; Zaynagutdinova, Elmira; Kruckenberg, Hulmut (Wildfowl, 2013)
Barnacle Geese Branta leucopsis first colonised the Russian arctic island of Kolguev in the early 1980s, since when their numbers have steadily grown. Initial colonies were founded on fox-free coastal sand spits, but by the mid-1990s large colonies (> 5,000 breeding pairs) had become established in the Peschanka River delta, reaching 45,000 breeding pairs by the mid-2000s. Subsequently, numerous new smaller colonies (mean ± s.d. = 12 ± 6 nesting pairs, range = 1–54, n = 18 colonies) started to increase in numbers in the central part of the island, initially associated with c. 30% of all known Peregrine Falcon Falco peregrinus nests in the study area. The overall population size and number of inland colonies continued to grow, and by 2011–2012 all 24 known Peregrine Falcon nests had Barnacle Goose colonies (mean colony size = 54 ± 40 pairs, range = 1–133, n = 13 colonies). White-fronted Geese Anser albifrons and Tundra Bean Geese Anser fabalis rossicus formerly recorded nesting in dense colonies around Peregrine Falcon nests no longer did so, apparently having been expelled from core areas by the earlier nesting and more aggressive Barnacle Geese. The hatching success of Barnacle Geese nesting in the open sedge-moss bogs of central Kolguev (first occupied in 2011–2012) was no different to those associating with Peregrine Falcons (73% and 75% respectively). During brood rearing and moulting, Barnacle Geese share feeding habitats with other goose species. Should their numbers continue to grow on the island, further overgrazing of foraging habitats may increase competition between Barnacle Geese and White-fronted Geese for food, both in brood-rearing and in moulting habitats.